PEREMPUAN BERHADAPAN DENGAN HUKUM PADA PERKARA CERAI GUGAT DALAM PERSPEKTIF IBNU QAYYIM: WOMEN FIGHTING WITH THE LAW IN DIVORCE CASES IN THE PERSPECTIVE OF IBNU QAYYIM - Parahdina, Soraya; Sa’dah, Rahimah Tul; Vizaini, Akhmad (Mitsaqan Ghalizan, 2022)
A woman who faces a law on a judicial divorce get a change of her right as a wife after the divorce. There are some arrangements about the right that woman gets when her husband divorce her as in QS. Al-Ahzab [33]: 49, QS. Al-Baqarah [2]: 236, and QS. Al-Baqarah [2]: 241. The husband must give mut’ah to the wife he divorced. As well as the arrangement in the Islamic Law Compilation, it only applies to the husband who divorces his wife and he must give mut’ah and nafkah iddah. However, for the divorce case whether it is in Al-Qur’an, the majority of ulama’s opinion, or the Islamic Law Compilation do not explain about it. Yet, as the time goes by, it is also affected by the changes of the situation in society, then the arrangement to accommodate the right after the divorce for judicial divorce is created. This article attemps to discuss about the relevance problem of Ibnu Qayyim’s opinion to the issue of the woman who faces a law on the judicial divorce case. The result of the research shows that Ibnu Qayyim’s theory about the changes of the law is very relevant to the problem that the writer takes.